Z prawnej problematyki spółdzielczości w rolnictwie - Suchoń, Aneta (Wydawnictwo Naukowe UAM, 2009)
The aim of the paper is to determine whether and to what extent the legislator facilitates the formation and functioning o f agricultural cooperatives under the conditions of the new political and economic system. The author concludes, that the legislator strives for a better organization and functioning of cooperatives active in agriculture by gradually introducing changes to various legal acts, including the law on cooperatives of 16 September 1982. However, this legislative activity is not sufficient. Specific provisions on agricultural cooperatives could be incorporated into a separate law. Such law would have to contain rules on particular cooperatives operating in the field of agriculture, i.e. on farm cooperatives, agricultural production cooperatives, agricultural circle cooperatives, dairy cooperatives and so called producer group cooperatives.

L’obiettivo dell'articolo è il tentativo di stabilire in quale misura il legislatore faciliti l’organizzazione e il funzionamento di cooperative agricole nelle nuove condizioni del sistema politico. In conclusione l’autrice constata che il legislatore cerca di facilitare l’organizzazione e il funzionamento di cooperatvie agricole, introducendo gradualmente delle modifiche ai diversi atti normativi, tra cui alia legge 16 setiembre 1982 diritto delle cooperative. Tale attivitá legislativa non è tuttavia sufficiente. Le norme speciali concementi le cooperative agricole potrebbero essere contenute nella legge speciale dedicata alle cooperative agricole, la quale dovrebbe comprendere le rególe riguardanti le singóle cooperative funzionanti nel settore agricolo. Si tratta, in particolare, di cooperative di agricoltori, di cooperative agricole produttive, di cooperative di circoli agricoli, di cooperative casearie, nonché di gruppi cooperativi di produttori agricoli.
From the legal problems of agricultural cooperatives
Sulle cooperative in agricoltura: alcune problematiche